Economically Potential Pigments from Marine Blue-Green Algae for the Application in Food and Health - Salim, Katarina Purnomo; Chandra, Rosita Dwi; Heriyanto, Heriyanto; Susilaningsih, Dwi; Limantara, Leenawaty; Brotosudarmo, Tatas H.P. (Ma Chung Research Center for Photosynthetic Pigments, 2019)
Current efforts to explore the potency of marine resources have been made to promote economic development in Indonesia, especially in the industrial sector. Marine cyanobacteria such as Arthospira sp. and Scytonema sp. are two potential candidates of the blue-green algae that can be used in the application for food and health industries. This study focused on the identification of the composition of the dominant chlorophylls and carotenoids. The results showed the presence of Zeaxanthin, Chlorophyll a, and Î²-carotene. The economic potency of those dominant pigments will be reviewed in this article.